Female and Male Features of Entrepreneurs and Employees before and During the Covid-19 Pandemic Recession: The Case of Poland - MONIKA RÓŻYCKA (Communications of International Proceedings, 2021)
The objective of the study is to show that when bringing new quality into the business world, the characteristics associated with women, are now considered to be more desirable in business and management. It presents the results of the empirical research into female and male entrepreneurs, carried out in the West Pomeranian Voivodeship in Poland before and during the Covid-19 pandemic. It is supported by the indication that the paradigm of the appreciation of women’s values in business can be observed for some time. The analyses conducted on the basis of the secondary information, including the bibliographic references, covering the national and foreign subject literature as well as the empirical research, and the obtained primary information, constituting the data obtained in the process of carrying out own research among entrepreneurial people in the West Pomeranian Voivodeship before the COVID-19 pandemic indicated the women who succeed in business represent strong female characteristics and strong male characteristics at the same time. Another research was carried out also in the area of the West Pomeranian Voivodeship during the COVID-19 pandemic and the task of the qualitative analysis showed that in the current crisis the best leaders are those characterized by empathy, sensitivity to human needs – employees and customers and striving to achieve results in the company at the same time. Communication focused on authenticity in communicating feelings and emotions, using frequent feedback, explaining and inspiring as a tactic of influence in gaining trust and commitment of employees also turned out to be important. Orientation to building and maintaining relationships is also very important during the crisis – which provides safety and comfort, as well as sharing knowledge and willingness to listen to the opinion of others before making a decision. These are also the characteristics – values associated with women. This method of management most strongly builds trust and strengthens bonds within the company. On the other hand, competition, focusing on pushing through one’s own opinion, concentrating on the performance of results above all and assertiveness turned out to be of little importance. These are the qualities – values associated as typically masculine.
Keywords: Entrepreneurship; paradigm of the appreciation of women’s values in business; COVID-19; female features; female management style